Cork – A Renewable Raw Material: Forecast of Industrial Potential and Development Priorities - Duarte, Ana Paula; Bordado, João Carlos (Frontiers in Materials, 2015)
This article aims to report the main applications of cork material from ancient times until nowadays, describing its industrial potential for other applications under study. It is also described the cork origin, the extraction process and the relationship between composition and cellular structure with properties.